Symmetrical cointegrating relationship between money supply, interest rates, consumer price index, terroristic disruptions, and Karachi stock exchange: Does global financial crisis matter? - Umaid A. Sheikh; Muzaffar Asad; Aqeel Israr; Mosab I. Tabash; Zahid Shahab Ahmed (Cogent Economics & Finance, 2020)
The study is intended to investigate the symmetrical relationship between macroeconomic variability and KSE-100 indexes by employing the ARDL model with bound testing procedure and error correction model. Authors have also examined whether the linkages between macroeconomic variability and KSE-100 indexes change in the wake of the 2008 Global economic recession. Macroeconomic variability is represented by fluctuations in interest rates, consumer price index, and Money supply (M2). Monthly level data representing macroeconomic volatility has been incorporated from the trading economics website and validated from the Pakistan bureau of statistics. Four different types of unit root tests like augmented dickey fuller test, KPSS, and Philips Peron unit root are also employed for the identification of seasonality effects in data. To identify structural breaks and linearity in data, the Zivot Andrew unit root test and BDS test for nonlinearity have also been employed respectively. This study adds to the existing literature by classifying investor's different reactions to fluctuation in macroeconomic variability before and after the international economic recession. Our study results proposed that in the long run and before the international economic crunch, the money supply and interest rates have an inverse relationship with stock indexes but CPI has a direct and significant relationship. However, after the 2008 economic crisis and for a longer horizon, stock indexes have been impacted positively by money supply, and IR has formulated an inverse relationship with KSE-100 indexes. This indicated that the association between macroeconomic variations and KSE-100 indexes changes following the 2008 international economic crisis.
Keywords: 330; ARDL with bound testing approach; BDS test for non-linearity; effect of terrorism on stock indexes; global financial crisis and stock indexes; macroeconomic volatility and stock indexes; time series modelling